Comparison of the effectiveness of using captopril and valsartan in thypertension patients with kidney failure at Citra Husada hospital - Anisa Agustina; Mayasari, Shinta; Nafisah Isnawati (Jurnal EduHealth, 2024)
Renal failure was a clinical condition characterized by irreversible decline in kidney function. Renal failure was divided into chronic and acute renal failure. Hypertension was a major factor triggering the occurrence of kidney disease and kidney failure. Data released by WHO shows that 50% of people with kidney failure, both acute and chronic, reach 50%. Based on Riskesdas, in 2018 the prevalence of chronic kidney failure in Indonesia was 0.38%. East Java Province was 0.3%, while the highest prevalence based on age was 65-74 years old at 8.23%. Effectiveness could provide information about how much a drug could achieve the desired effect in clinical practice. The purpose of this study was to compare the effectiveness of used captopril and valsartan in hypertensive patients with kidney failure at hospital. Methods: This research uses a numerical comparative analytical research type with an observational and cross-sectional design. The research was conducted at. Citra Husada Hospital in March-April 2023, using patient medical record data sources, and a sample of 64 patients. Data sources were analyzed using the Chi square test. Data is displayed in frequency and percentage form. Results: The results of this study showed that the average valued of blood pressure before administration of captopril was 183. 65 mmhg/99. The average value of blood pressure after administration of captopril was 171. 00 mmhg/91. 778 mmhg. The average value of blood pressure before administration of valsartan was 165. 87 mmhg/92. 81 mmhg. The average value of blood pressure after administration of valsartan was 151. 15 mmhg / 81. 09 mmhg. From the results of the studies, it was found that there was no difference between the comparison of the effectiveness of used captopril and valsartan in hypertensive patients with kidney failure at hospital. Conclusion: The conclusion of this study shows that there was no comparison of the effectiveness of used captopril and valsartan in hypertensive patients with kidney failure, both of which had the same effectiveness in lowering blood pressure